Implementation of Space Utilization Control Post Law Number 11 in the Year 2020 About Work Creation - Firmansyah, Arif; Jamilah, Lina; ., Irawati (KnE Social Sciences, 2023)
The implementation of spatial planning in Indonesia refers to Law Number 26 of 2007 concerning Spatial Planning and Law Number 11 of 2020 concerning Job Creation and its derivative regulations. Spatial planning, as stated in Article 3, “the implementation of spatial planning aims to create a safe, comfortable, productive, and sustainable national space based on the Archipelago Insight and National Resilience and the realization of the protection of space functions and prevention of negative impacts on the environment due to space utilization. In order to realize the objectives of spatial planning, these regulations must be enforced. The testing of the implementation of Law Number 26 of 2007 concerning spatial planning and Law Number 11 of 2020 concerning job creation was carried out with the theory of the legal system of Lawrance Friedman with normative juridical research methods. The approaches used were legal and conceptual. The results of the research show that the implementation of controlling space utilization after Law Number 11 of 2020 concerning job creation cannot be implemented properly, because the legislation in the field of spatial planning has not been able to support the control of space utilization. In addition, from law enforcement it is necessary to increase resources, such as human resources and infrastructure, the legal culture of the community. Keywords: implementation, spatial planning, legal system